Ground electromagnetic application in near surface investigation of a copper mineralization in the caÇapava do sul countryside (rs) - Bitencourt, Jorge da Cruz; Pereira, Henrique Garcia; Lima, José Pedro Rebés; Hansen, Marco Antonio Fontoura; Moreira, César Augusto [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
The service and maintenance of industrial and civil construction demands in relation to mineral inputs stimulates research to the discovery of new mineral deposits or the expansion of known deposits. The inductive electromagnetic geophysical method (EM) is widely used in studies involving the research of metallic minerals. In the search for copper the EM method is efficient because this metal behaves as an excellent conductor body in the presence of a magnetic field, which enables the distinction it from other rocky constituents by resulting high electric conductivity. This paper describes the application of the EM method for the mapping of mineralized fractures in the area of the Victor Teixeira cupper occurrence. The subsurface investigation was elaborated according to the preferred NW-SE tectonic alignment of the mineralized fractures previously obtained by the remote sensing data and supported by the attitudes obtained in the detail structural survey. The apparent conductivity sections showed high conductivity vertical anomalies (greater than 15 mS/m) to the locations where crossed the mapped fractures, suggesting the confirmation of the presence of subsurface copper mineralization in the area of the mineral occurrence studied.
Aplicação de método eletromagnético terrestre de investigação rasa numa ocorrência cuprífera localizada no interior do município de caçapava do sul (rs)
Keywords: Copper; Electromagnetic method; Remote sensing